A compact analytical design of dual-loop 18 GHz frequency synthesizer to enhance signal reliability in digital millimeter radio link system - Moghavvemi, M.; Ameri Mahabadi, H.; Attaran, A. (2011)
In this paper a high resolution dual-loop 17.7-19.7 GHz frequency synthesizer is presented which is compatible with ITU-R (F.595-6) standards. The investigations of phase noise and spur frequency contents are discussed in detail. The simulated and measured phase noise and spur frequency contents are similar to one another. Phase noise of -81 dBc/Hz in 17.7 GHz at 10 KHz offset frequency is measured by (HP8560) series Spectrum analyzer and it matches with predicted measurements.